Heat stress during late pregnancy of sows influences offspring longissimus dorsi muscle growth at weaning. (May 2021) - Li, Yanfei; Fan, Guoqiang; Liu, Yang; Yao, Wen; Albrecht, Elke; Zhao, Ruqian; Yang, Xiaojing
Abstract: In pregnant sows, heat stress (HS) not only affects sows, but also has long-term effects on offspring growth. However, it is still unclear how HS in pregnant sows influences offspring skeletal muscle development. In this study, 12 sows with similar body conditions were assigned into either a control (CON) or an HS group. The CON sows were housed at 18–22 ℃, and the sows in the HS group were housed at 28–32 ℃ from day 85 to 114 of pregnancy. The results showed that maternal HS decreased the total protein content ( P < 0.05) and prolactin level ( P < 0.05), yet increased the triglyceride content ( P < 0.05) of milk. The piglets of both groups had similar body weight and longissimus dorsi (LD) muscle weight at birth, but body weight ( P < 0.05) and LD weight ( P < 0.05) was significantly lower at weaning age in the HS group. Increased expression of myostatin (MSTN) ( P < 0.05) and its receptor ( P < 0.05) in the LD of HS piglets was observed at weaning. The following decreased in HS piglets: expression of serine/threonine-specific protein kinase ( P < 0.05), the mammalian target of rapamycin ( P < 0.05), and glycogen synthase kinase-3β ( P < 0.05) signal pathway-involved proteins. The results indicated that maternal HS during late pregnancy influenced offspring LD muscle growth via the activated MSTN pathway. This effect may be related to sow's milk composition. Highlights: Heat stress in late pregnancy affects the composition of colostrum in sows. The heat stress of sows in late pregnancy could affect the muscle development of weaned piglets. Heat stress in sows during late pregnancy affects muscle protein synthesis by affecting MSTN protein expression.